Spatial Variations in Factors Affecting Poverty - Mosley, Jane M.; Miller, Kathleen K. (University of Missouri - Columbia Institute of Public Policy, 2004)
There is abundant research that focuses on the causes and consequences of poverty in rural areas, and on the factors that ameliorate rural poverty. While a comprehensive review of this literature is not possible in this space, we summarize the research on differences in poverty between rural and urban areas, and how factors that ameliorate poverty differ between rural and urban areas. We focus primarily on studies that are national in scale, and that looked specifically at these spatial differences and effects. Both rural people and rural places are disadvantaged relative to their urban counterparts. Although a larger portion of the poor population resides in urban areas, poverty rates are higher and more persistent in rural areas (Adams and Duncan 1992; Summers et al. 1993; Iceland 2003), and research suggests poverty rates increase as rural areas become increasingly remote (Miller and Weber 2003; Lobao and Schulman 1991;see figure 1). Fisher and Weber (2002) find that poverty rates are highest in remote rural counties and central cities, and that these areas are quite similar on other outcome measures. RUPRI Rural Poverty Research Center Includes bibliographical references